Parallel computational fluid dynamics towards teraflops, optimization, and novel formulations : proceedings of the Parallel CFD '99 Conference - Parallel CFD '99 Conference (1999 : Williamsburg, Va.); Keyes, David E. (Amsterdam ; New York : Elsevier, 2000)
Contributed presentations were given by over 50 researchers representing the state of parallel CFD art and architecture from Asia, Europe, and North America. Major developments at the 1999 meeting were: (1) the effective use of as many as 2048 processors in implicit computations in CFD, (2) the acceptance that parallelism is now the 'easy part' of large-scale CFD compared to the difficulty of getting good per-node performance on the latest fast-clocked commodity processors with cache-based memory systems, (3) favorable prospects for Lattice-Boltzmann computations in CFD (especially for problems that Eulerian and even Lagrangian techniques do not handle well, such as two-phase flows and flows with exceedingly multiple-connected demains with a lot of holes in them, but even for conventional flows already handled well with the continuum-based approaches of PDEs), and (4) the nascent integration of optimization and very large-scale CFD. Further details of Parallel CFD'99, as well as other conferences in this series, are available at <SURL>http://www.parcfd.org</SURL>.
Includes bibliographical references.
Keywords: Fluid dynamics -- Data processing -- Congresses; Parallel processing (Electronic computers) -- Congresses; Electronic books